2013
DOI: 10.15296/ijwhr.2013.02
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyoma and Nutrition, a Case-Control Study

Abstract: Objectives: Uterine leiomyoma is one of the most common benign tumors of the uterus that causes so many problems for women such as uterine bleeding. Medical treatment of this disease is temporary so women may be compelied to hysterectomy that is definitive treatment of leiomyoma. Nowadays researches show that most of the diseases can be prevented by changing the life style. Researches emphasize the role of healthy nutrition in preventing the diseases, so the aim of this study is the comparison of nutrition in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
(13 reference statements)
1
3
0
Order By: Relevance
“…A more likely explanation is that citrus fruit may reduce uterine fibroids risk through pathways mediated by sex steroid hormones, antioxidants, or both (39) . This finding is congruent with that of Bani et al (2013) (36) who revealed that their mean score of fruits intake in healthy women was significantly more than women with myoma. Another study carried out by Wise et al (2011) (40) had investigated the intake of fruit, vegetables, and carotenoids in relation to risk of uterine leiomyomata.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A more likely explanation is that citrus fruit may reduce uterine fibroids risk through pathways mediated by sex steroid hormones, antioxidants, or both (39) . This finding is congruent with that of Bani et al (2013) (36) who revealed that their mean score of fruits intake in healthy women was significantly more than women with myoma. Another study carried out by Wise et al (2011) (40) had investigated the intake of fruit, vegetables, and carotenoids in relation to risk of uterine leiomyomata.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in accordance with the findings of He et al (2013) (33) who reported that vegetables and fruits intake were significantly inversely associated with fibroid risk. While Bani et al (2013) (36) who studied the leiomyoma and nutrition elaborated that the mean score of vegetables intake in healthy women was significantly more than women with myoma (p<0.05). Also, Chiaffarino et al (1999) (31) investigated the Diet and Uterine Myomas and found that a high intake of green vegetables seems to have a protective effect against uterine fibroids.…”
Section: Discussionmentioning
confidence: 96%
“…According to the purpose and type of the study and based on previous studies (20) in this field by taking into account the assumptions of error of 5%, power of 80%, an effect size of 50% and one to one ratio, 63 individuals in each group and a total of 126 people were estimated using the following formula.…”
Section: Study Design and Samplingmentioning
confidence: 99%
“…Surgical methods including dilatation and curettage (D & C), dilatation and evacuation (D & E), and P value = 0.00. suction curettage, even when performed by experienced surgeons (11)(12)(13), lead to cervical rupture, uterus perforation, and injury to the abdominal organs. Abortion is an alternative method which has been employed from 30 years ago due to fewer complications and appropriate responses in comparison with surgical procedures (14,15). So far, many studies have been conducted on various types of medical abortion, but few studies have considered the effects of estrogen priming on the success of induction.…”
Section: Discussionmentioning
confidence: 99%